2017
DOI: 10.1007/s10766-017-0495-0
|View full text |Cite
|
Sign up to set email alerts
|

3D-Stacked Many-Core Architecture for Biological Sequence Analysis Problems

Abstract: Sequence analysis plays extremely important role in bioinformatics, and most applications of which have compute intensive kernels consuming over 70% of total execution time. By exploiting the compute intensive execution stages of popular sequence analysis applications, we present and evaluate a VLSI architecture with a focus on those that target at biological sequences directly, including pairwise sequence alignment, multiple sequence alignment, database search, and short read sequence mappings. Based on coars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Accelerating Sequence Alignment. Another very recent prior work [65] exploits the high memory bandwidth and the reconfigurable logic layer of 3D-stacked memory to implement an accelerator for sequence alignment (among other basic algorithms within the sequence analysis pipeline). Many prior works (e.g., [13-16, 26, 35, 41, 70, 81, 82, 96]) use FPGAs to also accelerate sequence alignment.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Accelerating Sequence Alignment. Another very recent prior work [65] exploits the high memory bandwidth and the reconfigurable logic layer of 3D-stacked memory to implement an accelerator for sequence alignment (among other basic algorithms within the sequence analysis pipeline). Many prior works (e.g., [13-16, 26, 35, 41, 70, 81, 82, 96]) use FPGAs to also accelerate sequence alignment.…”
Section: Related Workmentioning
confidence: 99%
“…We have shown that GRIM-Filter significantly reduces the execution time of read mappers by reducing the number of unnecessary sequence alignments and by taking advantage of processing-in-memory using 3D-stacked DRAM technology. We believe there are many other possible applications for employing 3D-stacked DRAM technology within the genome sequence analysis pipeline (as initially explored in [65]), and significant additional performance improvements can be obtained by combining future techniques with GRIM-Filter. Because GRIM-Filter is essentially a seed location filter to be employed before sequence alignment during read mapping, it can be used in any other read mapper along with any other acceleration mechanisms in the genome sequence analysis pipeline.…”
Section: Future Workmentioning
confidence: 99%
“…(2019) argue the need for co-design; the design of the hardware acceleration and SRA software in parallel. This is especially true at scale, with more varied computational blocks included within the system ( Liu et al , 2017 ). Implementations such as ASAP ( Banerjee et al , 2019 ) and AligneR ( Zokaee et al , 2018 ) sufficiently illustrate this requirement in which edit distance computation is executed as a systolic array in parallel within dedicated electronic hardware rather than sequentially on CPUs.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to increase speed through closely coupling memory and computation, i.e. physically stacking computational blocks used for alignment with dedicated RAM has resulted in decreased accuracy, high energy consumption and high implementation costs ( Liu et al , 2017 ). As such, further scale in this regard produces diminishing returns.…”
Section: Opportunities In Short Read Alignment Accelerationmentioning
confidence: 99%
See 1 more Smart Citation